Geology, mineralogy, and cassiterite geochronology of the Ayawilca Zn-Pb-Ag-In-Sn-Cu deposit, Pasco, Peru - Benites, D. (2021)
This study was economically supported by the Peruvian CONCYTEC-FONDECYT-World Bank project 107-2018-FONDECYT-BM-IADT-AV and the Mexican research program CONACYT-Ciencia Básica (A1-S-14574). We thank the staff of Tinka Resources Ltd., particularly to Jorge Gamarra, for help and hospitality during the sampling program. We appreciate the technical support by Xavier Llovet (CCiT-UB) and Carlos Ortega Obregón (LEI-UNAM) during acquisition of EPMA data, and by Pete Tollan (ETH) during acquisition of LA-ICP-MS data. We are grateful to Richard Sillitoe, Andreas Dietrich, Graham Carman (president and CEO of Tinka Resources), and Editor-in-Chief Bernd Lehmann for their constructive comments which significantly improved the manuscript. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the U.S. Government.